Cerium-based nanoplatform for severe acute pancreatitis: Achieving enhanced anti-inflammatory effects through calcium homeostasis restoration and oxidative stress mitigation - Tingyi Luo; Yujing Tang; Wangcheng Xie; Zhilong Ma; Jian Gong; Yonggui Zhang; Tingsong Yang; Xuyang Jia; Jia Zhou; Zhengyu Hu; Lin Han; Qigang Wang; et al. (Materials Today Bio)
Severe acute pancreatitis (SAP), a life-threatening inflammatory disease of the pancreas, has a high mortality rate (∼40 %). Current therapeutic approaches, including antibiotics, trypsin inhibitors, fasting, rehydration, and even continuous renal replacement therapy, yield limited clinical management efficacy. Abnormally elevated calcium levels and reactive oxygen species (ROS) overproduction by damaged mitochondria are key factors in the inflammatory cascade in SAP. The combination of calcium chelators and cerium-based nanozymes loaded with catalase (MOF808@BA@CAT) was developed to bind intracellular calcium, eliminate excessive ROS, and ameliorate the resulting mitochondrial dysfunction, thereby achieving multiple anti-inflammatory effects on SAP. A single low dose of the nanoplatform (1.5 mg kg−1) significantly reduced pancreatic necrosis in SAP rats, effectively ameliorated oxidative stress in the pancreas, improved mitochondrial dysfunction, reduced the proportion of apoptotic cells, and blocked the systemic inflammatory amplification cascade, resulting in the alleviation of systemic inflammation. Moreover, the nanoplatform restored impaired autophagy and inhibited endoplasmic reticulum stress in pancreatic tissue, preserving injured acinar cells. Mechanistically, the administration of the nanoplatform reversed metabolic abnormalities in pancreatic tissue and inhibited the signaling pathways that promote inflammation progression in SAP. This nanoplatform provides a new strategy for SAP treatment, with clinical translation prospects, through ion homeostasis regulation and pancreatic oxidative stress inhibition.